Review of the book: Badr al-Din Muhammad b. Muhammad Kaysuni-zadeh Nidai-efendi (Remmal-khoja). The History of Khan Sahib Giray (Moscow, 2023) - Tatiana Anikeeva (Крымское историческое обозрение)
The review provides a brief overview of the publication of “The History of Khan Sahib Giray”, carried out in 2023 by I.V. Zaitsev and R.R. Abduzhemilev, which serves the urgent task of studying and publishing sources on the history of the Crimean Khanate and the history of Islam in Crimea. This work, according to I.V. Zaitsev, is the earliest historical work on the Crimean Khanate that has come down to our time (it was written after the assassination of the khan in 1551 and completed in the summer of 1553) and has the character of an absolute panegyric to the ruling khan. The chronicle of Remmal Khoja covers the actual period of the reign of Khan Sahib Giray I, ending with a description of his death, funeral and a request from his daughter Nur Sultan to write an essay. The publication is accompanied by two articles – by I.V. Zaitsev (“The History of Khan Sahib Giray”) and R.R. Abduzhemilev (“A literary view of the work of Remmal-khoja”), contains two texts of the translation of “The History of Khan Sahib Giray” and a facsimile of the chronicle list stored in the collection of the Library of the Oriental Faculty of St. Petersburg State University. The publication is provided with an indeces of names and geographical and ethnic names. This book contains not only translations of Remmal-Khoja’s work, made in two editions, but is the first publication of fragments of V.D. Smirnov’s work – in other words, this edition reflects a certain stage in the development of Russian Turkology.